Advances in frontier research on engineering structures : proceedings of the 6th International Conference on Civil Architecture and Structural Engineering (ICCASE 2022), Guangzhou, China, 20-22 May 2022.: proceedings of the 6th International Conference on Civil Architecture and Structural Engineering (ICCASE 2022), Guangzhou, China, 20-22 May 2022. Volume 1 (2023) - Unknown
No abstract available